Inner Retinal Layer Hyperreflectivity Is an Early Biomarker for Acute Central Retinal Artery Occlusion - Wenzel, Daniel A.; Poli, Sven; Casagrande, Maria; Druchkiv, Vasyl; Spitzer, Martin S.; Bartz-Schmidt, Karl Ulrich; Grohmann, Carsten; Schultheiss, Maximilian (Frontiers in Medicine, 2022)
Purpose: To investigate inner retinal hyperreflectivity on optical coherence tomography (OCT) as a potential biomarker indicating acute central retinal artery occlusion (CRAO). Methods: A total of 56 patients at two university hospitals with acute CRAO (symptom onset ≤ 48 hours) were included in this retrospective study. The optical intensity of the inner retinal layers was determined in both eyes and the relationship between symptom onset and inner retinal layer optical intensity in OCT scans compared to the unaffected fellow eye was analyzed. Several differential diagnoses (central retinal vein occlusion, anterior ischemic optic neuropathy, diabetic macular edema, subretinal fibrosis/disciform scar (Junius-Kuhnt) served as controls to validate optical intensity-based diagnosis of CRAO. Results: CRAO strongly correlated with an increased inner retinal layer hyperreflectivity in this cohort with acute CRAO with a time since symptom onset ranging from 1.1 to 48.0 hours. Receiver operating characteristic (ROC) analysis showed an area under the curve of 0.99 to confirm CRAO with a true positive rate of 0.93 and a false positive rate of 0.02. No correlation between optical intensity and time since symptom onset was noticeable. None of the differential diagnoses did show an elevated optical intensity of the inner retinal layers as it was detectable in CRAO. Conclusions: OCT-based determination of inner retinal layer hyperreflectivity is a very promising biomarker for a prompt diagnosis of CRAO in an emergency setting. This may be of major interest to speed up the administration of a possible thrombolytic treatment.